Analisa Pengaruh Paket Wisata Destinasi Pangalengan Terhadap Keuntungan Berdasarkan Skenario Pemodelan Menggunakan Aplikasi Anylogic (Studi Kasus : PT. Java Wisata) - Anida Wafiq Adawiyah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Tourism is the activity of temporarily moving people to destinations outside their place of residence and place of work and carrying out activities while at the destination as well as preparing facilities to meet their needs. The definition of tourism will never be precise among experts. Basically tourism is travel with the aim of entertaining which is carried out outside the daily activities carried out in order to provide benefits that are permanent or temporary. In Indonesia, the tourism sector is one of the supports for the country's economy, where Indonesia is a country that has natural beauty and cultural diversity so that it becomes an attraction for tourists to travel to Indonesia. In the current pandemic situation, tourism companies are also affected by the pandemic, including the Java Wisata company. Reporting from the Java Wisata website, the Java Wisata company itself is an official and licensed travel agency domiciled in Bandung. Java Wisata provides a choice of domestic and foreign tour packages, for domestic one of them is a tour package to Pangalengan tourist attractions in South Bandung, then for domestic tour packages Java Wisata provides tour packages to Malaysia. Java Wisata Tour Bandung not only provides tour packages, but we also provide meeting packages and adventure packages in Bandung. The RPD Rich Picture Diagram is an ideal tool for communicating complex problem situations. RPD shows the overall situation in one picture. In addition, RPD is also a modeling tool that depicts cartoons to describe the entire complex system so that it is easy to read from all points of view.